2014
DOI: 10.17221/7795-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary glycerin supplementation in the starter diet on broiler performance

Abstract: ABSTRACT:This study was conducted to evaluate the performance, carcass composition, and litter moisture of broiler chicks fed crude glycerin for 1-21 days. The study used 1056 male birds distributed in a completely randomized design, with six treatments (0, 3, 6, 9, 12, and 15% crude glycerin from 1 to 10 days), with eight replicates. After the 10 th day, each treatment group was divided into two groups out of which one continued to receive the same glycerin level and the second group started to receive a glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
2
12
0
3
Order By: Relevance
“…These results confirm those obtained by Cerrate et al (2006) and Guerra et al (2011), in which inclusion of 10% crude glycerin in broiler diets negatively affected their intake. Henz et al (2014) worked with glycerin inclusion (0, 3, 6, 9, 12, and 15%) in diets for broilers in the period of 1 to 10 days of age and also found a quadratic effect of the glycerin levels on feed intake, at the maximum level of 9.02%.…”
Section: Resultsmentioning
confidence: 88%
“…These results confirm those obtained by Cerrate et al (2006) and Guerra et al (2011), in which inclusion of 10% crude glycerin in broiler diets negatively affected their intake. Henz et al (2014) worked with glycerin inclusion (0, 3, 6, 9, 12, and 15%) in diets for broilers in the period of 1 to 10 days of age and also found a quadratic effect of the glycerin levels on feed intake, at the maximum level of 9.02%.…”
Section: Resultsmentioning
confidence: 88%
“…Alguns trabalhos com frangos de corte (Guerra et al 2011, Silva et al 2012, Henz et al 2014, poedeiras (Swiatkiewicz & Koreleski 2009, Duarte et al 2014) e codornas (Pasquetti et al 2014) vem sendo desenvolvidos, entretanto a composição das glicerinas utilizadas em cada estudo é bastante variável, principalmente em relação aos teores de sódio, cloro e metanol, o que é consequência do processamento do óleo ou gordura para obtenção do biodiesel, sendo muitas vezes contraditórias as definições aplicadas à glicerina resultante desse processo.…”
Section: Introductionunclassified
“…Apesar dessas limitações de uso da glicerina, os trabalhos demonstram bons resultados no desempenho das aves recomendando inclusões de 5 até 15% (Guerra et al 2011, Silva et al 2012, Henz et al 2014. Entretanto, torna-se imprescindível a abordagem de aspectos que evidenciem a interferência de componentes da glicerina na fisiologia e saúde do animal e sua relação com o desempenho, para que a glicerina se torne um ingrediente com baixa restrição do uso na alimentação animal.…”
Section: Introductionunclassified
“…Ustundag et al (2013) fed broilers diets containing 2.5% glycerine and observed increased feed intake, but no differences in feed efficiency (level of glycerine supplementation and feeding period did not affect this parameter). Henz et al (2014) revealed that dietary level of crude glycerine up to 6.06% resulted in better body weight gains without influencing carcass traits. Moreover, higher levels of glycerine (12 and 15%) resulted in lower weight gains, and increasing crude glycerine level quadratically increased feed intake at 10 days of age.…”
Section: Introductionmentioning
confidence: 98%